Comparison Of Main Pulmonary Artery Diameter Between Patients With Pulmonary Artery Hypertension And Asymptomatic Adults Using Computed Tomography - JEEVA S BENJAMIN; SUSHIL YADAV (International Journal of Pharma and Bio Sciences, 2015)
Right cardiac catheterization is considered to be the gold standard for measuring pulmonary artery pressure but this is an invasive procedure. An increase in the diameter of the pulmonary artery is a strong indication for the presence of pulmonary hypertension. Some investigators have found reasonable correlations with pulmonary arterial size and Pulmonary artery pressure PAP in studies with chest radiography. However measurement of the pulmonary artery diameter by chest radiography is poorly reliable as a method for the examination of pulmonary artery pressure. The objectives of this study were to estimate the main pulmonary artery diameter and compare main pulmonary artery diameter between patients with pulmonary artery hypertension and asymptomatic adults using computed tomography. Total of 46 subjects were included in the study which includes 23 pulmonary hypertensive cases and 23 non-pulmonary hypertensive subjects. The mean diameter in pulmonary hypertensive group was 31.79 ± 4.3 mm and for the non – hypertensive group mean diameter was 25.94 ± 2.4mm. Independent test was used for data analysis and the difference mean pulmonary artery diameter between two groups was found to be statistically significant with the confidence interval of 95%. Cut-off value of main pulmonary artery diameter was found to be 29.0 mm and had 82.60% sensitivity and 91.30% specificity for the detection of pulmonary hypertension.